Pengaruh Motivasi Terhadap Hasil Belajar Bahasa Jepang siswa Kelas X IPS 1 SMA Negeri Padang - salsabila fauziyyah adra (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2022)
This research is motivated by the assumption that motivation affects Japanese learning outcomes. The purpose of this study was to determine the effect of motivation on Japanese language learning outcomes for students of class X IPS 1 SMA Negeri 8 Padang.This research method is a quantitative method. This study using purposive sampling, namely the technique of determining the sample with certain considerations. The subjects of this study were all students of class X IPS 1 SMA Negeri 8 Padang totaling 38 people. The instruments used in this study were tests and non-tests. The test in this study was taken from the student learning outcomes document, while the non-test was a motivational questionnaire. The data processing technique uses a Likert scale (Very high = 4, High = 3, Normal = 2, Low = 1). The data analysis technique used a simple regression analysis technique to answer the motivational research on learning outcomes.The results of this study indicate that there is a positive and significant effect of learning motivation on learning outcomes of Japanese language subjects for students of Class X Social Sciences 1 SMA Negeri 8 Padang, a significance value of 0.045 <0.05 was obtained. With the value of r-square = 0.107, which means the influence/contribution of motivation to learning outcomes is 10.7%. In conclusion, motivation affects learning outcomes.